Correlation between Food Intake and Health Status with the Nutritional Status of School Children Age 9-11 in Semarang City - Ali, Aiman Farag Mohammed; Muis, Siti Fatimah; Suhartono, Suhartono (Biosaintifika: Journal of Biology & Biology Education, 2016)
Malnutrition, a major risk factor for a number of infectious diseases, including acute upper respiratory tract infections (AURTI), is common in developing countries. Nutritional status is an important index of the quality of life. Objectives:To analyze the correlation between food intake and health status to nutritional status of 9-11 years old children in Semarang. The study was a correlation study carried among school children in Semarang aged 9-11 years old. Data are presented in the descriptive analyses and Spearman correlation. Overall, food intake (energy and protein) of 9-11 years old children in Semarang is normal with ? 90% RDA, health status of them was satisfactory (very low AURTI incidence),and their nutritional status were mostly normal. There was a correlation between energy intake with nutritional status with indicators BMI, and z-score of W/A and H/A, but there was no correlation between protein intake and AURTI with nutritional status. Energy and food intake of the children correlate with all nutritional status being studied. It should be suggested to parents to implement balanced diet, to avoid the development of obesity among elementary school children through nutrition education to prevent malnutrition as well as obesity.How to CiteAli, A. F. M., Muis, S. F., & Suhartono, S. (2016). Correlation between Food Intake and Health Status with The Nutritional Status of School Children Age 9-11 in Semarang City. Biosaintifika: Journal of Biology & Biology Education, 8(3), 249-256.